Quality criteria for medical device registries: best practice approaches for improving patient safety - a systematic review of international experiences - Niederländer, Charlotte; Kriza, Christine; Kolominsky-Rabas, Peter (Expert Review of Medical Devices, 2017)
INTRODUCTION: As the benefit of medical device registries (MDRs) depends on their content and quality, it is important to ensure that MDRs have a robust and adequate structure to fulfill their objectives. However, no requirements are specified for the design and content of MDRs. The aim of this work is to analyze different MDRs in the field of implants and to give best practice recommendations for quality criteria regarding their design and development. Areas covered: A systematic literature search performed in databases (Medline, Cochrane Library, Scopus, Embase, CRD York), selected journals and websites identified 66 articles describing either a general MDR structure or the development process of specific registries. Extracted information about MDRs served as the basis for recommendations: MDRs should deliver a minimal data set and report information about the geographical area, data collection, numbers of patients enrolled, registry staff, and security and confidentiality of data. Expert commentary: Well-structured registries are a cornerstone of the regulatory process of medical devices and a major tool for decision makers. A future goal is to establish agreed minimal data sets for different devices - overcoming national borders. By establishing clear guidelines, the outcomes as well as registry comparability can be fundamentally improved.
EVALuna2:33842